Lnc-PKD2-2-3/miR-328/GPAM ceRNA Network Induces Cholangiocarcinoma Proliferation, Invasion and 5-FU Chemoresistance - Zhang, Lei; Ma, Donglai; Li, Fujun; Qiu, Gongcai; Sun, Dongsheng; Zeng, Zhaolin (Frontiers in Oncology, 2022)
Purpose Our previous study observed that long non-coding RNA PKD2-2-3 (lnc-PKD2-2-3) is related to advanced tumor features and worse prognosis in cholangiocarcinoma (CCA). Then, this study aimed to further explore the linkage between lnc-PKD2-2-3, miR-328, and GPAM, as well as their effects on regulating CCA viability, mobility, and chemosensitivity. Methods Lnc-PKD2-2-3, miR-328, and GPAM expression in 30 pairs of CCA tumor and adjacent tissues, as well as in CCA cell lines, were determined. Two CCA cell lines (HuCCT1 and TFK1) were transfected by lnc-PKD2-2-3 overexpression plasmid, lnc-PKD2-2-3 siRNA, miR-328 inhibitor, and GPAM siRNA alone or in combination, followed by cell proliferation, apoptosis, invasion, and 5-FU chemosensitivity detection. Besides, xenograft mice were established for validation. Results Lnc-PKD2-2-3 and GPAM were higher, whereas miR-328 was lower in CCA tissues versus adjacent tissues and also in CCA cell lines versus control cells; meanwhile, they were correlated with each other (all P <0.05). Lnc-PKD2-2-3 knockdown decreased CCA cell proliferation, invasion, and increased apoptosis (all P <0.05), but lnc-PKD2-2-3 overexpression exhibited the opposite and weaker effect. MiR-328 knockdown induced CCA cell proliferation and invasion and also attenuated the effect of lnc-PKD2-2-3-knockdown in these functions (all P <0.05). Subsequently, GPAM knockdown reduced CCA cell proliferation and invasion and also weakened the effect of miR-328-knockdown in these functions (all P <0.05). Additionally, lnc-PKD2-2-3 positively regulated GPAM while negatively regulating miR-328. MiR-328 negatively modified GPAM in CCA cells. Luciferase gene reporter assays verified that lnc-PKD2-2-3 directly bound miR-328 and miR-328 directly bound GPAM. Finally, the lnc-PKD2-2-3/miR-328/GPAM network also regulated the 5-FU chemosensitivity of CCA cells. In vivo experiments further revealed that lnc-PKD2-2-3 overexpression promoted tumor volume and weight but repressed tumor apoptosis in xenograft mice; meanwhile, it increased GPAM expression but decreased miR-328 expression (all P <0.05). Conversely, lnc-PKD2-2-3 knockdown exhibited the opposite effects (all P <0.05). Conclusion Lnc-PKD2-2-3/miR-328/GPAM ceRNA network promotes CCA proliferation, invasion, and 5-FU chemoresistance.